1999
DOI: 10.1046/j.1365-2443.1999.00276.x
|View full text |Cite
|
Sign up to set email alerts
|

Intragenic suppression of trans‐dominant lethal substitutions in the conserved GEME motif of the β subunit of RNA polymerase: evidence for functional cooperativity within the C‐terminus

Abstract: Background: The ubiquitous multimeric RNA polymerases contain two large, conserved subunits, of which the ␤ subunit has been implicated in all three stages of transcription. We have previously described a genetic system involving random, PCR-mediated mutagenesis of the region of rpoB encoding the C-terminal 116 amino acids of the ␤ subunit of Escherichia coli RNA polymerase and the characterization of dominant-negative mutations. This study identified the invariant motif GEME (residues 1271→1274; Cromie et al.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2009
2009
2012
2012

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 30 publications
0
2
0
Order By: Relevance
“…Extensive mutagenesis of the second largest subunit, rpoB in E.coli revealed that mutations within all four GEME motif amino acids result in dominant phenotypes when the mutant subunit is produced from a plasmid at similar levels to the chromosomal encoded non-mutant copy [56]. Substitutions in this region produced a RNA polymerase that competed with the wild type RNA polymerase complex potentially because the mutant polymerase was blocked after transcription initiation [56],[73]. The strength of the dominant phenotypes varied depending on the specific substitution.…”
Section: Discussionmentioning
confidence: 99%
“…Extensive mutagenesis of the second largest subunit, rpoB in E.coli revealed that mutations within all four GEME motif amino acids result in dominant phenotypes when the mutant subunit is produced from a plasmid at similar levels to the chromosomal encoded non-mutant copy [56]. Substitutions in this region produced a RNA polymerase that competed with the wild type RNA polymerase complex potentially because the mutant polymerase was blocked after transcription initiation [56],[73]. The strength of the dominant phenotypes varied depending on the specific substitution.…”
Section: Discussionmentioning
confidence: 99%
“…Third, changes in protein sequence under a nonprogressive evolutionary model may be viewed as intragenic suppression, where a change in one residue with a deleterious effect is compensated by selection of a second change in sequence that restores the original function. This process of selecting for intragenic suppressor mutations to maintain original structure and function has been proposed to explain paired mutations in HIV-1 protease (Parera et al, 2009), cytochrome c oxidase subunit I (Acín-Pérez et al, 2003), b-subunit of RNA polymerase (Malik et al, 1999), and aminoacyl-tRNA synthetase (Ador et al, 2004) and for the complementary bases in the double-stranded stems of structural RNAs (e.g., tRNA, rRNA, small nuclear RNA, etc.). A comparison of the sequences and three-dimensional structures (see Supplemental Figures 2 and 3 online) of At-ACT2 and Hs-ACTB suggests that their evolution from a common ancestral actin occurred by the codivergence of sets of adjacent amino acids.…”
Section: Discussionmentioning
confidence: 99%